Physiology, pharmacology and prospects for dipeptidilpeptidase-4 inhibitors use - D. V. Kurkin; D. A. Bakulin; E. I. Morkovin; A. V. Strygin; Yu. V. Gorbunova; E. V. Volotova; I. E. Makarenko; V. B. Saparova; R. V. Drai; V. I. Petrov (Фармация и фармакология (Пятигорск))
Modern requirements for the treatment of type 2 diabetes mellitus (DM2) include not only achieving a glycemic control, but also reducing the risk of developing cardiovascular complications. Dipeptidyl peptidase 4 (DPP-4) inhibitors are inferior in the effectiveness to some other actively developing groups of hypoglycemic drugs (SGLT2 inhibitors and GLP-1 receptor agonists); however, they seem relevant at the present time.The aim of the study is to analyze the literature data on the therapeutic potential and results of the of DPP-4 inhibitors research.Materials and methods. When searching for the review article materials, the abstracting databases of PubMed, Google Scholar and e-Library were used. The search was carried out on the publications for the period from 2006 to 2022, using the following keywords: DPP-4 inhibitors; glucagonlike peptide-1 (GLP-1); glucose-dependent insulinotropic peptide (GIP); sitagliptin, and other drugs.Results. DPP-4 belongs to the serine proteases family and is involved in the degradation of various chemokines and peptide hormones, including incretins secreted by intestinal L- and K-cells – GLP-1 and GIP. They regulate a postprandial insulin secretion and a β-cell function, modulate a fasting and postprandial glucagon secretion, regulate the eating behavior and have many pleiotropic (immunomodulatory, anti-inflammatory, antifibrotic, etc.) effects. DPP-4 inhibitors reduce an enzyme activity by 70–90%, increasing plasma incretin levels by 2–4 times and have been used to treat DM2 since 2006. Now there are 13 DPP-4 inhibitors on the market in different countries, differing primarily in pharmacokinetic parameters. They are actively used in the combination therapy for type 2 diabetes, increasing the glycemic control effectiveness without increasing the risk of hypoglycemia. The evidence is emerging about the therapeutic potential of DPP-4 inhibitors in COVID-19.Conclusion. A peroral form, an ability to create effective combinations with other hypoglycemic drugs without increasing the risk of hypoglycemia, the pleiotropic effects of DPP-4 inhibitors, make this group relevant at the present time.